BIOETHICS IN MEDICINE: MODERN CONCEPTS AND PRINCIPLES - Васкес Абанто Х. Е.; Васкес Абанто А. Е.; Арельяно Васкес С. Б. (World of Medicine and Biology, 2015)
During the reformation the health system of many countries thinking of people about the Hippocratic oath, which is nothing other than a symbol may not be the most appropriate for today also needs "reformat". It is needed to consider more real principles of moral in medicine, necessarily pluggings in itself normatively – legal aspects of public relations. In this connection bioethics is called to be the same instrument.Issues of ethics, morality and bioethics affect swingeing majority of population, a fortiori since almost everybody in one or another measure appears the consumer of health services, called to come forward as the informed and autonomous subject (patient or examinee) of making decision.In the modern world it is needed to consider more real principles of moral in medicine, necessarily pluggings in itself normatively – legal aspects of public relations. In this connection bioethics(principle of "respect of rights and dignity of man") is called to be a the same instrument.Ethics and morality of the medical officer are a natural reflection of the true personal and professional formation, which in turn can significantly influence on his human qualities.The range of ethical issues, including issues arising from the relationship of the subjects of medical activities in health, which is designated by the term "bioethics" (and in this context: ethics, deontology, moral), is directly related not only to the duties but to the rights as a medic, and other entities data relationships. In modern society to talk about rights and responsibilities - means implemented in the legislation.As well as in other issues, facts are preceded to the theory and undoubtedly exactly because of the crimes and violations appearance of the ethic codes and the rules became possible. Every new rule for the ethic adjusting of the human researches condemns the violations and is nothing more than an attempt to avoid them in the future, creating obligations and new credit of the trust given to the scientific experiments on human.Today's development of biomedical technologies requires of the creation of ethic and legislative conception of clinical practice and scientific researches according to the present development of medicobiological, chemical and pharmaceutical science, and also requirements of psycho-social factor.Carrying out of the biomedical researches is considered as illegal, unconscionable, amoral and even criminal action. If the regulations and the norms of the law will not be observed this is entail penal offence.The ethic orientation of the medical activity and the realization of the researches fully depend on a professional competence and morality of the medical employee (practical physician-worker, researcher etc.).For today, the medical association came to common opinion, that a doctor-scientist can not be higher than the universal values. At a decision-making, equally with the scientific interests, which, undoubtedly, will bring to development of the theoretical and practical medicine, a doctor must take into account moral values.
Keywords: ethics; bioethics; morality; medicine; collegiality; medical relations